2000
DOI: 10.1128/mcb.20.3.1021-1029.2000
|View full text |Cite
|
Sign up to set email alerts
|

PR48, a Novel Regulatory Subunit of Protein Phosphatase 2A, Interacts with Cdc6 and Modulates DNA Replication in Human Cells

Abstract: Initiation of DNA replication in eukaryotes is dependent on the activity of protein phosphatase 2A (PP2A), but specific phosphoprotein substrates pertinent to this requirement have not been identified. A novel regulatory subunit of PP2A, termed PR48, was identified by a yeast two-hybrid screen of a human placental cDNA library, using human Cdc6, an essential component of prereplicative complexes, as bait. PR48 binds specifically to an amino-terminal segment of Cdc6 and forms functional holoenzyme complexes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
117
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(119 citation statements)
references
References 47 publications
0
117
2
Order By: Relevance
“…This gene encodes a subunit of a serine/threonine phosphatase, which exerts regulatory control over DNA replication initiation. 13 The deletion of this gene was thought unlikely to be the cause of the observed short stature and no further analysis was undertaken at this time point.…”
Section: Resultsmentioning
confidence: 99%
“…This gene encodes a subunit of a serine/threonine phosphatase, which exerts regulatory control over DNA replication initiation. 13 The deletion of this gene was thought unlikely to be the cause of the observed short stature and no further analysis was undertaken at this time point.…”
Section: Resultsmentioning
confidence: 99%
“…22 Importantly, we have shown that in every case the mutation renders the A␣ subunit defective in binding B or C subunits, depending on whether the mutation is located in the N-terminal B subunit binding domain (repeats 1-10) or in the C-terminal C subunit binding region (repeats [11][12][13][14][15] (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…The A and C subunits both exist as 2 isoforms (␣ and ␤ ), whereas the B subunits fall into 3 families designated B, [2][3][4][5] , BЈ (also called B56) 6 -10 and BЉ. [11][12][13][14] A model demonstrating how the A, B and C subunits interact in the holoenzyme is shown in Figure 1. 15,16 The existence of so many regulatory subunits suggests that the various forms of PP2A have distinct functions.…”
mentioning
confidence: 99%
“…The B' family consists of numerous isoforms and splice variants whose molecular masses range from 54 ± 68 kDa (Csortos et al, 1996;McCright et al, 1996;McCright and Virshup, 1995;Tanabe et al, 1996;Tehrani et al, 1996). The B'' family has at least four members, designated PR48, PR59, PR72 and PR130 (Hendrix et al, 1993;Nagase et al, 1997;Voorhoeve et al, 1999;Yan et al, 2000). PR72 and PR130 are splice variants of the same gene.…”
Section: Introductionmentioning
confidence: 99%